Brachial artery diameter, but not flow-mediated dilation, is associated with sleep apnoea in the Multiethnic Study of Atherosclerosis. Issue 3 (March 2016) - Atkinson, Greg; Danjoux, Gerard; Ells, Louisa; Suri, Sophie; Batterham, Alan M.
Abstract : Background: The percentage flow-mediated dilation (FMD%) of the brachial artery is purported to be an early indicator of atherosclerosis and has been reported to be reduced in people with obstructive sleep apnoea. Nevertheless, FMD% scales poorly for, and is concomitantly dependent on, initial artery diameter, which may, itself, be higher in obstructive sleep apnoea patients. Therefore, for the first time, we aimed to quantify the differences in initial diameter and properly scaled flow-mediated dilation between people with and without sleep apnoea. Method: The prevalence of physician-diagnosed sleep apnoea, as well as initial and peak diameters of the brachial artery were recorded for 3354 participants in the Multiethnic Study of Atherosclerosis (MESA). Arterial data were analysed using FMD% and an allometric approach, which scales the flow-mediated response properly for initial diameter. Results: In the sex, race and age-adjusted model, initial diameter was 0.19 mm larger in sleep apnoea patients [95% confidence interval (CI): 0.07 to 0.32 mm, P = 0.003] and correlated negatively with FMD% ( r = −0.43, 95% CI: −0.57 to −0.26, P < 0.0005). Using this same adjusted model, FMD% was 3.8 ± 2.7% for sleep apnoea patients ( n = 104) versus 4.4 ± 2.7% for undiagnosed people (95% CI for difference: −1.12 to −0.07%, P = 0.028). Allometric scaling halved this FMD%-indicated sample difference in flow-mediated dilation (95% CI: −0.7 to 0.1%, P = 0.19). Conclusion: The initial diameter of the brachial artery is larger in MESA participants diagnosed with sleep apnoea compared with undiagnosed people. However, the difference in flow-mediated dilation between these two cohorts is trivial, when the flow-mediated response is scaled properly for resting diameter.